Moving towards carbon neutral lifestyle through FinTech social media platform: a case study of Ant Forest - Shao, Zi; Xu, Yishuang (Frontiers in Environmental Science, 2023)
The escalating environmental crisis resulting from high carbon consumption has led to severe consequences, with natural disasters such as heavy rainfall, floods, and droughts inflicting significant damage upon both human society and the natural environment. Urgent measures to reduce carbon emissions are imperative. By integrating big data, social media, and mobile payment into a gamified participatory communication project, Ant Forest makes it easier for people to carry out low-carbon behaviours. However, limited knowledge exists regarding the impact of the use of new social media products led by Ant Forest on users' environmental behaviour and carbon neutral lifestyle, this study aimsed to explore such impact. This study constructsed an integrated new theoretical framework based on Theory of Reasoned Action (TRA), Diffusion of Innovation Theory (DIT), Knowledge-Attitude-Behaviour Theory (KAB), and Reinforcement Learning (RL). Structural Equation Modeling (SEM) iswas adopted to analyse data collected through the survey. In addition, semistructured interviews were have been takenused to understand the impact of Ant Forest on participants' lifestyle changes. The results suggest that beliefs, norms, entertainment interaction, and commonweal have significantly positive impacts on the citizen's act to use Ant Forest. Through knowledge sharing, Fintech social media products (Ant Forest) can promote users' environmental attitude and engender corresponding lowcarbon behaviours. This study provides inspiration for businesses and governments working to facilitate the transition to a low-carbon society and the adoption of carbon-neutral lifestyles.